The Unpredictable Species : What Makes Humans Unique - Lieberman, Philip (Princeton University Press, 2013)
The Unpredictable Species argues that the human brain evolved in a way that enhances our cognitive flexibility and capacity for innovation and imitation. In doing so, the book challenges the central claim of evolutionary psychology that we are locked into predictable patterns of behavior that were fixed by genes, and refutes the claim that language is innate. Philip Lieberman builds his case with evidence from neuroscience, genetics, and physical anthropology, showing how our basal ganglia--structures deep within the brain whose origins predate the dinosaurs--came to play a key role.